Commonwealth Caribbean Sports Law - Haynes, Jason; Marcus, J. Tyrone (Milton : Routledge, 2018)
Sports Law has quickly developed into an accepted area of academic study and practice in the legal profession globally. In Europe and North America,Sports Law has been very much a part of the legal landscape for about four decades, while in more recent times, it has blossomed in other geographic regions, including the Commonwealth Caribbean. This book recognizes the rapid evolution of Sports Law and seeks to embrace its relevance to the region. This book offers guidance, instruction and legal perspectives to students, athletes, those responsible for the administration of sport, the adjudication of sports-related disputes and the representation of athletes in the Caribbean. It addresses numerous important themes from a doctrinal, socio-legal and comparative perspective, including sports governance, sports contracts, intellectual property rights and doping in sport, among other thought-provoking issues which touch and concern sport in the Commonwealth Caribbean. As part of the well-established Routledge Commonwealth Caribbean Law Series, this book adds to the Caribbean-centric jurisprudence that has been a welcome development across the region. With this new book,the authorsassimilate the applicable case law and legislation into one location in order to facilitate an easier consumption of the legal scholarship in this increasingly important area of law.
3.3 Contractual capacity3.4 Interpretation of sports contracts; 3.5 Terms of sports contracts; 3.5.1 Common terms in players' contracts; 3.5.2 Common terms in coaches' contracts; 3.6 Player transfers; 3.7 Training compensation; 3.8 Sports agents; 3.8.1 The expertise of sports agents; 3.8.2 The role of sports agents; 3.8.3 Sports agents' fiduciary duties; 3.8.4 Agents' remuneration; 3.9 Breach of sports contracts; 3.10 Inducing a breach of contract; 3.11 Remedies; 3.11.1 Damages; 3.11.1.1 Damages on a loss of a chance basis; 3.11.1.2 Liquidated damages; 3.12 Mitigation; 3.13 Injunctions
Description based upon print version of record.
3.14 Restraint of trade
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Law and legislation -- West Indies, British; Liability for sports accidents -- West Indies, British; Doping in sports -- Law and legislation -- West Indies, British; LAW / International